Comparative anatomy of the facial artery of Sus scrofa scrofa (Linnaeus, 1758) (Mammalia, Suidae) - Machado Vieira, Tiago; de Assis Ribeiro, Lucas; Ozanam Carneiro e Silva, Frederico; Inhauser Riceti Magalhães, Henrique; Henrique de Paula, Ygor; Braz Romão, Fabiano; Borges Barcelos, Jeferson; Angélica de Carvalho-Barros, Roseâmely (Biotemas, 2017)
The wild boar is broadly distributed in several parts of the world by man, with the exception of Antarctica. It is known that the facial artery and its branches are responsible for maintaining the blood supply of structures related to chewing, swallowing, and the production of saliva. The aim of this study is to describe the origin and distribution of the right and left facial arteries of the boar in the context of foraging. The facial arteries of this boar species originated from the external carotid artery in all specimens and were distributed in the pharyngeal, glandular, and muscular branches as well as the branches to the mandibular lymph nodes. The anastomotic branches of the facial artery with the buccal and mylohyoid branch of the inferior alveolar artery were also identified. This feature shows that the region of allocation of the facial artery in these animals requires a large network for irrigation, which contributes to the functional efficacy as well as the modus viventis of this animal. O javali encontra-se amplamente distribuído pelo homem em diversas partes do mundo, com exceção da Antártica. É sabido que a artéria facial e seus ramos são responsáveis por manter o suprimento sanguíneo das estruturas relacionadas com a mastigação, deglutição e produção de saliva. Diante do exposto, objetivou-se descrever as origens e distribuições das artérias faciais direita e esquerda do javali. As artérias faciais deste suídeo originaram-se da artéria carótida externa em todos os espécimes e distribuíram-se em ramos faríngeo, glandulares, musculares e ramos para linfonodos mandibulares. Ramos anastomóticos da artéria facial com a bucal e com o ramo milo-hioideo da artéria alveolar inferior foram identificados. Essa característica demonstra que a região de alocação da artéria facial nesses animais necessita de um expressivo contingente para irrigação, colaborando muito com sua eficácia funcional, bem como com o modus viventis deste animal.